Implementasi Kegiatan Keagamaan Dan Peduli Lingkungan Pada Siswa Sekolah Menengah Pertama Negeri 2 Salatiga - Rizky Maulana Aziz; Badrut Tamami; Subhan Adi Santoso (Jurnal Mahasiswa Pendidikan, 2022)
The emergence of Covid-19 has had a tremendous impact on the world of education. To prevent the spread of the virus, the government has imposed large-scale restrictions. So that it has an impact on religious activities and care for the environment of students. This study aims to determine the form of implementation, the supporting and inhibiting factors of religious activities and environmental care for the students of Public Junior High School 2 Salatiga. This type of research is qualitative research. Sources of data used include primary sources, namely the results of interviews from school principals, teachers, and students; and secondary sources can be in the form of documents and photos of religious activities and care for the environment. Techniques in analyzing data using data reduction, data presentation, and conclusions. The results of this study indicate that Public Junior High School 2 Salatiga has: 1) The forms of implementation of students' religious activities include reading the Qur'an, reading Asmaulhusna, reading prayers, habituation of fardu prayers, habituation to giving alms, Islamic holidays, and Religious Extracurriculars; 2) Factors supporting the implementation of students' religious activities are the role of parents, school facilities and infrastructure, the commitment of Islamic Religion Teachers, and the environment around the school; 3) The inhibiting factors for the implementation of student religious activities are the Covid-19 pandemic and the diverse backgrounds of students. 4) The forms of implementation of student environmental care activities are the Adiwiyata Program, maintaining class cleanliness, planting plants, disposing of garbage in its place, waste management, energy saving, washing hands, wearing masks, keeping a distance, consuming nutritious and hygienic food, giving Covid-19 vaccines., and regular exercise; 5) Supporting factors for implementing student environmental care activities are school facilities and infrastructure and the Covid-19 pandemic; 6) The inhibiting factor for implementing student environmental care activities is the Covid-19 pandemic and the lack of awareness of students.